An investigation of the influence of the coating on the tool lifetime and surface quality for ultra-small micro end mills with different diameters. (May 2022) - Aurich, Jan C.; Kieren-Ehses, Sonja; Mayer, Tobias; Bohley, Martin; Kirsch, Benjamin
Abstract: Micro milling tools are subjected to high abrasive wear and the probability of tool breakage rises with the decrease in tool diameter. Coatings can help to counteract abrasive wear and to increase tool life. In this paper, micro milling tools with diameters of 50 μm, 25 μm, 12.5 μm and 6 μm are coated with a 200 nm thick TiB2 layer and applied to machine commercially pure titanium. The achieved feed travel as well as the slot bottom quality is evaluated qualitatively and the roughness quantitatively via confocal microscopy. For the first time, ultra-small micro end mills with diameters below 50 μm were able to fabricate microstructures in commercially pure titanium in a robust process. Results show that a superior tool life can be achieved via coating, especially for the smallest diameters. This enables a more productive generation of ultra-small microstructures.